MENGHARGAI MARTABAT PENYANDANG DISABILITAS : TIDAK ADA ALASAN UNTUK MENCARI SIMPATI DALAM MENGEMIS (International Forum of Researchers and Lecturers, 2023)
Cultivate a attitude to appreciate the reality of life of disabled people and understand that seeking is not always the desired choice to be the background in this research.The purpose of this study is so that people with disabilities do not be seen by society on their own eyes of the people with disabilities who are using their shortcomings to attract sympathy.The systematic method of literature review became the method used in this research.The study of the theory, The fact is that economic empowerment is one way to lift the dignity of disabled people.The conclusion, appreciating the reality of life of disabled people must be a fundamental attitude in society, Government should be more responsive in addressing this phenomenon because disabled people are also citizens whose rights must be fulfilled.